Macroeconomics : understanding the global economy - Miles, David , 1959-; Breedon, F. J. [ (Francis J.)]; Scott, Andrew , 1965- (John Wiley & Sons, 2012)
"A revised and updated edition of a very successful macroeconomics textbook. The authors deal with sophisticated issues using advanced economic theory, but in a manner that is accessible to anyone taking a single course in macroeconomics. They begin with real-world economic issues, and describe why these matter, before embarking on economic theory, ensuring that readers emerge with a good practical understanding of the global economy and how economists think about it"--Provided by publisher